BODY IDENTITY IN BOHUMIL HRABAL’S NOVEL “I SERVED THE KING OF ENGLAND” - Bokshan, Halyna (Літературний процес: методологія, імена, тенденції, 2019)
The purpose of the paper is to examine the specificity of the modeling of the character-narrator’s body identity in B. Hrabal’s novel “I Served the King of England”. Firstly it stresses on the body-centered nature of the narration in this literary work, in which the evolution of personality is represented as “a history of the body”. The study focuses on the techniques of restructurizing “the body scheme” and the manifestation of psychophysiological transgression caused by the existing “archetypal canons”. It traces the correlation of the semantics of the body identity with the aesthetic categories of the beautiful and the ugly and with gender differentiation. The paper also considers gastronomy as one of the aspects of bodiliness in B. Hrabal’s novel. It details the poetics of grotesque which manifests itself in the descriptions of the body emphasizing its objectiveness. The study looks at the Rabelaisian traditions followed by the writer in the depiction of the scenes connected with eating both everyday food and exotic dishes. The research underlines that the body in B. Hrabal’s novel is displayed as a genetic data medium, visualized through physical characteristics, that highlights the social arrangement of the body identity problems. It pays attention to the social function of a human face in archaic societies originally interpreted in the novel. The research determines the peculiarities of the space marking of the body in the literary work and its correlation with the binary opposition “top–bottom”. It looks at the formation of the body identity by means of a mirror reflection and the image of the double. The conclusions of the research emphasize the specificity of the modeling of the body identity in the novel of the Czech writer. The results of this scientific paper can be used in further research on B. Hrabal literary prose and in comparative studies examining typological parallels in visualizing bodliliness in his works and those of Yu. Vynnychuk. DOI: https://doi.org/10.28925/2412-2475.2019.131